2011
DOI: 10.1103/physrevb.84.081203
|View full text |Cite
|
Sign up to set email alerts
|

Infrared probe of the insulator-to-metal transition inGa1xMnxAsandGa<

Abstract: We report infrared studies of the insulator-to-metal transition (IMT) in GaAs doped with either magnetic (Mn) or non-magnetic acceptors (Be). We observe a resonance with a natural assignment to impurity states in the insulating regime of Ga1−xMnxAs, which persists across the IMT to the highest doping (16%). Beyond the IMT boundary, behavior combining insulating and metallic trends also persists to the highest Mn doping. Be doped samples however, display conventional metallicity just above the critical IMT conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…Generally speaking, these observations are consistent with the previous studies of (Ga,Mn)As ternary alloys where several authors have reported a moderate dependence of the MO properties on the Mn concentration. 11,25,26,30,31,34 It is worth mentioning that the spectral dependence of the magneto-optical Kerr effect obtained using the 40-band k.p model in (Ga,Mn)(As,P) is in much better agreement with experimental results than in ternary (Ga,Mn)As using the 30-band k.p model. 30 We believe that the more accurate description of the MOKE originates from a better description of the bands with our 40-band k.p model in particular, from a good determination of the BS details over a wide range of k-vectors in four directions.…”
Section: Moke Spectrasupporting
confidence: 72%
See 1 more Smart Citation
“…Generally speaking, these observations are consistent with the previous studies of (Ga,Mn)As ternary alloys where several authors have reported a moderate dependence of the MO properties on the Mn concentration. 11,25,26,30,31,34 It is worth mentioning that the spectral dependence of the magneto-optical Kerr effect obtained using the 40-band k.p model in (Ga,Mn)(As,P) is in much better agreement with experimental results than in ternary (Ga,Mn)As using the 30-band k.p model. 30 We believe that the more accurate description of the MOKE originates from a better description of the bands with our 40-band k.p model in particular, from a good determination of the BS details over a wide range of k-vectors in four directions.…”
Section: Moke Spectrasupporting
confidence: 72%
“…In the ferromagnetic SC (Ga,Mn)As, MO spectroscopy in the visible and infrared spectral regions has been used to gain insight into the controversial issue of the energy position of the Fermi level, inside the valence band (VB) or in an impurity band detached from the VB. [11][12][13][14][15][16] The prediction and experimental determination of MO spectra are also of prime importance to select the optimal wavelength for the optical investigation of static and dynamical magnetic properties. Optically detected hysteresis cycles obtained from the MOKE provide information on the magnetic anisotropy and magnetization reversal processes.…”
Section: Introductionmentioning
confidence: 99%
“…87 We note that there are a lot of papers supporting the IB conduction picture by using various methods recently. [88][89][90][91][92][93] In Fig. 12(a), the triangular red, circular blue, and rectangular green points show the E F values of Ga 1-x Mn x As, [(In 0.53 Ga 0.47 ) 1-x Mn x ]As, and In 0.87 Mn 0.…”
Section: -11mentioning
confidence: 99%
“…In this latter system, holes originating from Mn acceptors are the principal mediators of ferromagnetism 23,24 . Hallmark signs of itinerant FM observed in IR spectra of Ga 1−x Mn x As include an increase of the low energy "Drude" spectral weight with the development of magnetization 27,62 , and scaling of T C with the IR spectral weight over the intragap energy range 28,63 . We do not observe an increase of the low energy spectral weight upon crossing T C in our Mn-doped sample.…”
Section: B Mn-doped Bi2te3mentioning
confidence: 99%
“…These processes include the excitation of IR active and Raman active phonons, the electrodynamic response of charge carriers, both those in the bulk and potentially those on the surface, optical transitions initiated from mid-gap defect states, and excitations across the bulk energy gap. More importanly, however, IR spectroscopy is a well established tool for investigating ferromagnetism in semiconductors [25][26][27][28][29] . In particular, carrier mediated mechanisms have specific signatures in the IR.…”
Section: Introductionmentioning
confidence: 99%